2020
DOI: 10.3390/foods9121820
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Determination of Acrolein in Cider by 1H NMR Spectrometry

Abstract: Acrolein occasionally appears in cider, completely spoiling its quality due to its bitter taste. It is crucial to detect it in the early steps, before the taste is severely affected, to apply the appropriate treatment. A simple and rapid analytical method to determine this compound in cider is therefore desirable. In this work, a quantitative determination method of acrolein in cider is proposed using the proton nuclear magnetic resonance technique (1H NMR). Acrolein produces a doublet signal in the spectrum a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Likewise, compared with the C3G data, we found that the 1 H NMR spectrum of C3G−2ACR was similar to that of C3G, except that the two proton signals at δ H 6.64 (H-6) and 6.87 (H-5′) in the 1 H NMR spectrum of C3G had disappeared, suggesting that ACR groups linked with C3G at the positions of C-6 in the A-ring and C-5′ in the B-ring. We also discovered that there was one additional set of proton signals (δ H 2.71 m, 2H; δ H 2.16 m, 2H; δ H 5.86 m, 1H) for the ACR group in the 1 H NMR spectrum and one additional set of carbon signals (δ C 14.90, δ C 25.77, and δ C 93.39) for the ACR group in the 13 C NMR spectrum, and the data were similar to C3G−ACR in which one ACR group was attached at C-7 in the A-ring of C3G. In addition, another additional set of proton signals (δ H 2.81 m, 2H; δ H 2.03 m, 2H; δ H 5.80 m, 1H) for the ACR group in the 1 H NMR spectrum and another additional set of carbon signals (δ C 14.64, δ C 25.63, δ C 93.59) in the 13 C NMR spectrum for the ACR group were also observed.…”
Section: ■ Materials and Methodsmentioning
confidence: 87%
See 4 more Smart Citations
“…Likewise, compared with the C3G data, we found that the 1 H NMR spectrum of C3G−2ACR was similar to that of C3G, except that the two proton signals at δ H 6.64 (H-6) and 6.87 (H-5′) in the 1 H NMR spectrum of C3G had disappeared, suggesting that ACR groups linked with C3G at the positions of C-6 in the A-ring and C-5′ in the B-ring. We also discovered that there was one additional set of proton signals (δ H 2.71 m, 2H; δ H 2.16 m, 2H; δ H 5.86 m, 1H) for the ACR group in the 1 H NMR spectrum and one additional set of carbon signals (δ C 14.90, δ C 25.77, and δ C 93.39) for the ACR group in the 13 C NMR spectrum, and the data were similar to C3G−ACR in which one ACR group was attached at C-7 in the A-ring of C3G. In addition, another additional set of proton signals (δ H 2.81 m, 2H; δ H 2.03 m, 2H; δ H 5.80 m, 1H) for the ACR group in the 1 H NMR spectrum and another additional set of carbon signals (δ C 14.64, δ C 25.63, δ C 93.59) in the 13 C NMR spectrum for the ACR group were also observed.…”
Section: ■ Materials and Methodsmentioning
confidence: 87%
“…We also discovered that there was one additional set of proton signals (δ H 2.71 m, 2H; δ H 2.16 m, 2H; δ H 5.86 m, 1H) for the ACR group in the 1 H NMR spectrum and one additional set of carbon signals (δ C 14.90, δ C 25.77, and δ C 93.39) for the ACR group in the 13 C NMR spectrum, and the data were similar to C3G−ACR in which one ACR group was attached at C-7 in the A-ring of C3G. In addition, another additional set of proton signals (δ H 2.81 m, 2H; δ H 2.03 m, 2H; δ H 5.80 m, 1H) for the ACR group in the 1 H NMR spectrum and another additional set of carbon signals (δ C 14.64, δ C 25.63, δ C 93.59) in the 13 C NMR spectrum for the ACR group were also observed. The key HMBC showed that the proton at δ H 2.81 was correlated with δ C 93.59 (C-16), δ C 25.63 (C-15), and δ C 112.62 (C-5′), implying that another ACR group was linked to the C-5′ position in the B-ring of C3G.…”
Section: ■ Materials and Methodsmentioning
confidence: 87%
See 3 more Smart Citations